The Locked Room and Other Horror Stories: level 4 - James M. R. (Penguin Readers)
A tree full of enormous spiders; curtains like a dead man`s hair; an old man with no heart. These are some of the things you will discover in these terrifying short stories. We dare you to read this book! But if you do you won`t be able to put it down! M. R. James is one of the best writers of ghost and horror stories ever